Circular RNA Circ-BANP Regulates Oxidized Low-density Lipoprotein-induced Endothelial Cell Injury Through Targeting the miR-370/Thioredoxin-interacting Protein Axis. Issue 3 (March 2021) - Chen, Guang; Li, Yongjun; Zhang, Ailing; Gao, Lijun
Abstract : Abstract: Dysfunction of endothelial cells is now recognized as an important contributor to the pathogenesis of atherosclerosis (AS). Circular RNAs (circRNAs) have been demonstrated to be involved in AS pathogenesis. The purpose of this study was to explore the biological action of circRNA BTG3–associated nuclear protein (circ-BANP, hsa_circ_0040824) on the dysfunction of human umbilical vein endothelial cells (HUVECs) induced by oxidized low-density lipoprotein (ox-LDL). The levels of circ-BANP, miR-370, and thioredoxin-interacting protein (TXNIP) were gauged by quantitative real-time polymerase chain reaction or Western blot. The subcellular fractionation assay was used to determine the localization of circ-BANP, and the ribonuclease R assay was performed to evaluate the stability of circ-BANP. Cell viability, apoptosis, migration, invasion, and tube formation abilities were assessed by the Cell Counting Kit-8, flow cytometry, transwell, and tube formation assays. The levels of interleukin-6, tumor necrosis factor-α, and interleukin-1β were detected by enzyme-linked immunosorbent assay. Targeted relationships among circ-BANP, miR-370, and TXNIP were confirmed by a dual-luciferase reporter assay. Our data showed that circ-BANP expression was upregulated in AS blood and ox-LDL-induced HUVECs. The inhibition of circ-BANP promoted cell viability, migration, invasion, tube formation, and repressed cell inflammation and apoptosis in ox-LDL-induced HUVECs, demonstrating that circ-BANP silencing alleviated ox-LDL-induced HUVEC injury. Mechanistically, circ-BANP directly targeted miR-370. Moreover, miR-370 mediated the regulation of circ-BANP in ox-LDL-induced cell injury in HUVECs. TXNIP was a target of miR-370, and miR-370 overexpression relieved ox-LDL-induced HUVEC injury by downregulating TXNIP. Furthermore, circ-BANP modulated TXNIP expression by targeting miR-370. Our findings demonstrated that circ-BANP regulated ox-LDL-induced cell injury in HUVECs at least in part through targeting the miR-370/TXNIP axis, illuminating circ-BANP as a potential target for AS detection and treatment. Abstract : Supplemental Digital Content is Available in the Text.